THE DOMANIK FORMATION OF THE TIMAN-PECHORA BASIN: RADIOLARIANS, BIOSTRATIGRAPHY, AND SEDIMENTATION CONDITIONS - Afanasieva M.S.; Mikhailova M.V. (My University, 2001)
A diverse radiolarian assemblage of 127 species was studied for the first time from the middle Frasnian Domanik Formation of the Timan-Pechora province. The availability of sponge spicules, acritarchs, and rhizomorphs is proved. After a detailed analysis of macerated radiolarians, three subassemblages (lower Rdm-1, middle Rdm-2, upper Rdin-3) of substantially different quantitative and qualitative composition were distinguished in the Moskovistella allbororum-Ceratoikiscum ukhtensis radiolarian assemblage. Echinate species of Aculearia prevail over spherical Sphaerellaria forms, and this suggests a relatively cold conditions in bottom water mass. Cyclically changing taphocoenoses testify to significant ecological rearrangements during the Domanik time. A new interpretation of depositional conditions for Domanik Formation sediments in the southern Timan-Pechora basin of Russia is presented.